TMET-14. TUMOR-ASSOCIATED MYELOID CELL-DERIVED CREATINE PROMOTES GLIOBLASTOMA GROWTH IN HYPOXIC NICHES AND PSEUDOPALISADING TUMOR REGIONS. (14th November 2022) - Zolp, Andrew; Rashidi, Aida; Chia, Tzu-Yi; Dmello, Crismita; Arrieta, Victor; Zhao, Junfei; Castro, Brandyn; Markwell, Steven; Heiland, Deiter Henrik; Brat, Daniel; Chandel, Navdeep; Lesniak, Maciej; et al.
Abstract: Glioblastoma (GBM) consists of a unique tumor microenvironment (TME) dominated by infiltrating tumor-associated myeloid cells (TAMCs). TAMCs are central to tumor growth and understanding how they support tumor progression is critical to identifying new therapeutic modalities. Examination of the metabolic and genetic phenotypes of TAMCs revealed that the de-novo creatine phenotype is central to their identity. Immunohistochemistry and multiplex fluorescence in GBM patient-derived tissue showed TAMC infiltration localizing to hypoxic pseudopalisading regions. Furthermore, single-cell RNAseq analysis of human and mouse models of GBM identified that the transporter of creatine, Slc6a8, is located on tumor cells within these regions. Spatial transcriptomics confirmed this transporter-synthesis gene compartmentalization is specific to hypoxic pseudopalisading regions, and further elucidated a radial glial cell gene signature for tumor cells expressing Slc6a8. Murine models recapitulated the TAMC de-novo creatine metabolic phenotype both ex-vivo and in-vitro. Metabolomics showed that TAMC-derived creatine can transfer to tumor cells in-vitro and is enhanced under hypoxic conditions. β-guanidinopropionic acid (β-GPA) is a creatine analog proposed to block Slc6a8 function and effectively blocked TAMC-derived creatine transfer to tumor cells in-vitro. Furthermore, β-GPA inhibited both the viability and size of spheres for tumor cells grown in stem-cell conditions. Lastly, inhibition of creatine transport using clinically relevant inhibitors enhanced survival following tumor implantation in murine models. This work highlights the key role of creatine in the pseudopalisading and hypoxic niche in GBM, offering evidence for a potential benefit in targeting this axis for GBM therapy regimens.